CORRELATION BETWEEN COGNITIVE FUNCTION AND SERUM LEVELS OF TUMOR NECROSIS ALPHA (TNF-α) IN SCHIZOPHRENIA - Eldi Sauma; Antania Hanjani Irianti; Tuti Kurnianingsih; Shelly Iskandar; Sumartini Dewi; Veranita Pandia (Faculty of Medicine, Universitas Andalas, 2024)
Introduction: Impaired cognitive function causes significant impairment in schizophrenic patients. Studies result found that inflammatory processes in the brain play an important role in cognitive decline in schizophrenia. One of the inflammatory markers associated with cognitive function in schizophrenia is serum Tumor Necrosis Factor Alpha (TNF-α) levels. TNF-α levels can be influenced by genetic and racial factors. Objective: This study aims to analyze the correlation between cognitive function and TNF-α serum levels in schizophrenic patients in Indonesia. Methods: This study is an analytical study using a cross-sectional design in 34 schizophrenic patients who were hospitalized in the Mental Hospital of West Java Province. Patients with risk of inflammation and cognitive impairment are excluded. Cognitive function was assessed using the Rey Auditory Verbal Learning Test (RAVLT), Digit Span and Trail Making Test. TNF-α serum levels were measured using the Sandwitch-ELISA (Enzyme-linked Immunosorbent Assay) method. Results: Study participants showed a cognitive deficit in all examination instruments. The TNF-α serum levels of the participants increased (mean: 8.93 ± 3.43). TNF-α serum levels was not significantly correlated with cognitive function. Conclusion: There is no significant correlation exist between cognitive function and TNF-α serum levels in schizophrenia.Keywords: Schizophrenia, cognitive function, TNF-α